Răspuns:
2x+1=-5
2x=-5-1
2x=-6
x=-6:2
x=-3
0,5x-1,3=2,7
0,5x=2,7+1,3
0,5x=4
x=4:0,5
x=8
[tex]\sqrt{3}[/tex]x=2[tex]\sqrt{6}[/tex]
x=2[tex]\sqrt{6}[/tex]:[tex]\sqrt{3}[/tex]=2[tex]\sqrt{2}[/tex]
2) 2(x+1)-3(2-x)=x+3(2x+1)
2x+2-6+3x=x+6x+3
2x+3x-x-6x=3-2+6
-2x=7
x=-7:2
x=-3,5
3) inlocuim pe x cu -1
3+2(-1)-(-1-8)=-3(-1)+7
3-2+9=3+7
10=10
-1 este solutie
4) 3(2x-1)+3(x+1)-2(x-5)=15(8-x)
6x-3+3x+3-2x+10=120-15x
6x+3x-2x+15x=120+3-3-10
22x=110
x=110:22
x=5
5) -2x+3(x-3)+[tex]\frac{x-1}{2}[/tex]=[tex]\frac{x+1}{2}[/tex]-[tex]\frac{x+3}{6}[/tex]
[tex]\frac{x-4x+6x-18+x-1}{2}[/tex]=[tex]\frac{3x+3-x+3}{6\\}[/tex]
6(3x-19)=2(2x+6)
18x-4x=12+114
14x=126
x=126:14
x=9
inlocuim pe x=9
9m-3+18=2(m-9)+5
9m+15=2m-18+5
9m-2m=-18-15+5
7m=-28
m=-28:7
m=-4
6) |3x+5|=8
3x+5=8
3x=8-5
3x=3
x=3:3
x=1
Explicație pas cu pas